International apportionment mechanisms for VAT inputs - Is the turnover basis the best mechanism for all retail industries in South Africa? - Ritchie, Monique Adrienne (Department of Finance and Tax, 2015)
Apportionment of input VAT and the mechanisms used to calculate apportionment have been a challenging issue since the inception of the Value-Added Tax Act No. 89 of 1991 in South Africa. This requirement to apportion input VAT has particular relevance to the retail industry due to the increase in the extension of credit which results in the receipt of taxable supplies (ordinary sales) and exempt supplies (interest income). As retailers are therefore making mixed supplies, they are required to apportion the input VAT paid on expenses. At present the standard method for input VAT apportionment in South Africa is the turnover basis however this method is not perceived as equitable by credit retailers. After an in-depth analysis of the retail industry in South Africa, its relevance to the South African economy and the impact of the requirement to apportion input VAT using the turnover method on listed companies within the South African retail industry, this paper analyses the treatment of VAT apportionment by the South African Revenue Service within the context of the Value-Added Tax Act No. 89 of 1991 and relevant South African case law. Recommendations for South Africa are then sought by studying the mechanisms for input VAT apportionment used in countries with VAT systems similar to that of South Africa. Included in this study are those countries which employ traditional VAT systems such as European Union member states and Mexico; and those countries which have implemented modern VAT systems such as New Zealand, Singapore, Australia and Canada. In addition, alternative approaches to address the root cause of the requirement to apportion input VAT used internationally are researched to the extent that these mechanisms have application to the retail industry in South Africa.